Drying characteristics of distillers wet grains under varying condensed distillers solubles and drying temperature levels - Bhadra, Rumela; Rosentrater, Kurt A.; Muthukumarappan, Kasiviswanathan; Kannadhason, Sankaranandh (My University, 2011)
Distillers dried grains with solubles (DDGS) has been shown to be an excellent livestock feed ingredient, and it is produced by the fuel ethanol industry, which is primarily located in the Midwest United States. There is a growing need to transport DDGS over long distances via rail, but this can often be hampered by poor flowability when unloading. DDGS is formed by combining condensed distillers solubles (CDS) with distillers wet grain (DWG) and then drying at high temperatures. It is hypothesized that drying conditions can affect resulting DDGS chemical, physical, and flow properties, but there is currently little quantified information about drying behavior of these coproducts. Thus, the objective of this study was to investigate the moisture desorption patterns of DWG for three CDS addition levels [10%, 15%, and 20% wet basis (wb)] at three drying temperatures (100 ° C, 200 ° C, and 300 ° C), to thus produce DDGS. Several mathematical models (Page, Newton, Pilosof, Henderson-Pabis, and others) were used to fit the observed moisture data over time. A new comprehensive model was developed for moisture ratio versus time (the best fit had R ² = 0.91, SEM = 0.17) using a modified Page model which accounted for varying CDS and temperature levels. The developed model will be useful to predict moisture content values of DDGS for various drying times, CDS addition levels, and drying temperatures, and will thus be a benefit to industrial processing conditions.
Keywords: CDS; DDGS; DWG; Desorption; Drying; Moisture content; Moisture ratio; Page model